2005
DOI: 10.1177/0146621604271268
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Experiment to Compare Conventional, Computerized, and Computerized Adaptive Administration of Ordinal Polytomous Attitude Items

Abstract: A total of 520 high school students were randomly assigned to a paper-and-pencil test (PPT), a computerized standard test (CST), or a computerized adaptive test (CAT) version of the Dutch School Attitude Questionnaire (SAQ), consisting of ordinal polytomous items. The CST administered items in the same order as the PPT. The CAT administered all items of three SAQ subscales in adaptive order using Samejima's graded response model, so that six different stopping rule settings could be applied afterwards. School … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…Only very short CATs consisting of 1 or 2 items led to administration mode effects, but for these CATs, differences between the CT and the CAT group were limited to the variances. Hol et al (2005) compared a PPT, a CT, and a CAT in an experimental study, which also involved a motivation scale of 48 polytomous items. They detected small but inconsequential CAT administration mode effects, which however were greatest for the shortest CATs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only very short CATs consisting of 1 or 2 items led to administration mode effects, but for these CATs, differences between the CT and the CAT group were limited to the variances. Hol et al (2005) compared a PPT, a CT, and a CAT in an experimental study, which also involved a motivation scale of 48 polytomous items. They detected small but inconsequential CAT administration mode effects, which however were greatest for the shortest CATs.…”
Section: Discussionmentioning
confidence: 99%
“…These studies all showed that CAT can substantially reduce the number of administered items, while maintaining a high correlation between CAT latent trait (y estimates) and y estimates that were based on the entire item pool. Additionally, the studies by Hol et al (2001Hol et al ( , 2005 and MacDonald (2003) showed that reducing the number of administered items by CAT administration did not appreciably affect correlations with other criteria.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Computerized adaptive testing (CAT) based on item response theory (IRT) models seems like a natural solution, and there have been several applications of CAT technology in the attitudinal and personality domains. Some of these applications have utilized dominance IRT models (e.g., Hol, Vorst, & Mellenbergh, 2005;Simms & Clark, 2005;Waller & Reise, 1989), whereas others have been based on ideal point IRT models (e.g., Roberts, Lin, & Laughlin, 2001). Yet the common thread here is that items have consisted of individual statements requiring respondents to indicate their level of agreement using a dichotomous or polytomous response format.…”
Section: Introductionmentioning
confidence: 99%
“…3. La demostración de las ventajas de los modelos politómicos para el diseño TAIs e¿ cientes (Hol, Vorst & Mellenbergh, 2005;Lai, Cella, Chang, Bode & Heinemann, 2003;Van Rijn, Eggen, Hemker & Sanders, 2002), para la medición del DIF (Kim, Cohen, Alagoz & Kim, 2007) y para la igualación de puntuaciones (Lee, Kolen, Frisbie & Ankenmann, 2001). 4.…”
unclassified